Systematic Literature Review: Science Self-Efficacy in Science Learning - Kartimi Kartimi; Indah Rizki Anugrah; Istiqomah Addiin (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2021)
Abstract:Learning success is often represented by numbers that indicate the extent to which students can achieve educational goals. However, basically, the success is determined by how much effort and their self-efficacy in learning. Therefore, the purpose of this study is to describe students' self-efficacy in learning and teachers' self-efficacy in teaching science. To obtain more comprehensive data and explanations, the Systematic Literature Review method was used in this study. This method is used to analyze 168 articles indexed by Google Scholar. In general, the stages of this research include planning, conducting, and reporting. The research was conducted by referring to three research questions, namely (1) How is the student's self-efficacy in learning science?, (2) How is the teacher's self-efficacy in teaching science, and (3) how is the relationship between self-efficacy and other variables. The results obtained indicate that Science Self-efficacy in students can be raised by familiarizing students to obtain success in learning science while in teachers it is raised through teaching practicum training. This research is expected to provide an overview for researchers and teachers to develop self-efficacy in science learning.Abstrak:Kesuksesan belajar sering direpresentasikan dengan angka yang menunjukkan sejauh mana siswa dapat mencapai tujuan pendidikan. Namun, pada dasarnya kesuksesan terebut ditentukan oleh seberapa besar usaha dan self-efficacy mereka dalam belajar.. Oleh karena itu, tujuan penelitian ini adalah memaparkan Self-efficacy siswa dalam belajar dan Self- efficacy guru dalam mengajar IPA. Untuk memperoleh data dan penjelasan yang lebih mendalam, metode Systematic Literature Review digunakan dalam penelitian ini. Secara umum tahapan penelitian ini mencakup planning, conducting dan reporting. Penelitian dilakukan dengan mengacu pada tiga pertanyaan penelitian, yaitu (1) Bagaimana Self-efficacy siswa dalam belajar IPA?, (2) Bagaimana Self-efficacy guru dalam mengajar IPA dan (3) Bagaimana keterkaitan antara Self-efficacy dan variabel lainnya. Hasil yang diperoleh menunjukkan bahwa Science Self-efficacy pada siswa dapat dimunculkan dengan membiasakan siswa untuk memperoleh kesuksesan dalam pembelajaran IPA sedangkan pada guru dimunculkan melalui pelatihan praktikum mengajar.